Pendidikan Kesehatan Dalam Upaya Pencegahan Kanker Serviks Pada Wanita Usia Subur - Vio Nita; Novi Indrayani (Universitas Lancang Kuning, 2020)
In Indonesia, cervical cancer (cervical cancer) is the second most common cancer among women after breast cancer. Some factors causing cervical cancer are late detection by women due to lack of knowledge about cervical cancer, for example to maintain the cleanliness of the female area (vagina) is very important especially for women. The purpose of this study was to determine the knowledge of Pre and Post health education in efforts to prevent cervical cancer in women of childbearing age in Ringinsari Bokoharjo Hamlet Prambanan Sleman Yogyakarta. The method used is quasi experiment with the